Sabbath and Sunday, Passover and Easter, Judaism in the Afternoon: Jewish Time in the Galician Public School - Maślak-Maciejewska, Alicja (Instytut Historii im. Tadeusza Manteuffla Polskiej Akademii Nauk, 2024)
The public elementary schools (in practice established due to educational reforms of the late 1860s and early 1870s) and secondary schools operating in Galicia were legally open to children of all faiths, including Jews. However, in practice, these schools adapted to the needs of Christian children. Most Galician Jews who received a secular education and fulfilled compulsory schooling requirements, which were increasingly more effectively enforced during the autonomy period, attended these schools. This article analyses how Jewish time functioned in these institutions. It examines three key issues: the rhythm of the week (respecting the right to observe the Sabbath), the religious education provided at school (scheduling of classes and the simultaneity of religious instruction for children of different faiths), and the school year’s rhythm (particularly the religious holiday calendar according to which the school year was organised). Despite legislation allowing Jewish students to observe the Sabbath and religious holidays, living according to Jewish time proved challenging. The scheduling of religious instruction for Jewish students demonstrates their unprivileged position in the Galician school.
p. 33-54
Keywords: schooling in Galicia; Jewish education; Jews in public school; time; religious education; public schools - Galicia (Poland and Ukraine) - history; Jewish youth - education - Galicia (Poland and Ukraine); Jews - education - Galicia (Poland and Ukraine) - history; Galicia (Poland and Ukraine) - religious life and customs; time - religious aspects - history